Protocols using detomidine and oxytocin induce ex copula ejaculation in stallions - Cavalero, T. M.S. [UNESP] (2019)
Tricyclic antidepressives, such as imipramine, indirectly induce ejaculation by increasing the noradrenaline concentration, which triggers an α-adrenergic response, whereas α-adrenergic agonists, such as xylazine and detomidine, directly trigger ejaculation by activating the α-1 adrenergic receptors. Furthermore, serum oxytocin concentrations in stallions increase drastically before ejaculation, but decline immediately thereafter, implicating the role of this hormone in emission. The objectives of the present study were to: 1) compare the efficiency of various protocols for inducing ex copula ejaculation in stallions, 2) evaluate the benefits of including oxytocin in the protocols, and 3) compare the semen characteristics of ex copula versus in copula ejaculates. Nine protocols were used to induce ex copula ejaculation using various combinations of xylazine (X; 0.66 mg/kg, iv); oxytocin (O; 20 IU, iv), imipramine (I; 3 mg/kg, orally), and detomidine (D; 0.02 mg/kg, iv). Imipramine was given 2 h prior to the administration of α-adrenergic agonist (detomidine or xylazine) and oxytocin. If ejaculation did not occur within 10 min after treatment with an α-adrenergic agonist, a half-dose of the same product was injected. Twelve sexually mature stallions (6–26 y) were used; 9 of 12 stallions responded to the treatment. Two stallions responded to X or XO, four stallions responded to IX and IXO, one stallion responded to DO, and five responded to IDO. Stallions that responded to detomidine did not respond to xylazine. No stallion ejaculated in response to D, ID, or IO. Erections and masturbation occurred only in imipramine-treated stallions. Sperm quality was similar among all the protocols and was not significantly different from those in in copula ejaculates collected with an artificial vagina. In a separate trial, none of these protocols induced ex copula ejaculation in 2–3 y old stallions. The side effects included sialorrhea after imipramine administration in all the stallions and sedation after administration of xylazine or detomidine. In conclusion, the new protocol, IDO, and the traditional protocol, IX, had similar results, with IDO being a useful alternative protocol in stallions for which IX was not effective. Therefore, attempts using both the protocols are encouraged, as stallions that ejaculated upon administration of detomidine did not ejaculate when xylazine was administered, whereas those that responded to xylazine did not respond to detomidine.